Data Mining with Big Data: It’s Issues and Challenges - Namdev, Swati (International Journal of Computer Sciences and Engineering, 2019)
Big Data could be a new term wont to determine the datasets that because of their large size and complexity. Big Data are currently speedily increasing altogether science and engineering domains, as well as physical, biological and medical specialty sciences. Big Data processing is that the capability of extracting helpful data from these large datasets or streams of data, that because of its volume, variability, and velocity, it absolutely was unfeasible before to try to to it. The Big data challenge is turning into one in every of the foremost exciting opportunities for the following years. This paper includes the knowledge concerning what is Big Data, Data Mining, Data Mining with Big Data, Challenging issues and its related work.